2020
DOI: 10.5194/egusphere-egu2020-1421
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Nitrogen addition accelerates ecosystem phosphorus cycling at multiple scales in a temperate grassland of Northeast China

Abstract: <p>Plant phosphorus (P) resorption, mutualistic symbiosis with mycorrhizas, such as arbuscular mycorrhizal fungi (AMF) and soil organic P mineralization are crucial strategies for acquiring sufficient P to meet plant nutrient demand. Which is the main strategy, however, responding to elevated nitrogen (N) addition to alleviate P deficiency caused by N enrichment remains unclear in terrestrial ecosystems. We explored the responses of foliar P resorption of dominate species (Leymus chinensis), soil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
2
3
0
Order By: Relevance
“…Thus, our experimental findings indicate that deep mowing slightly altered the composition of soil bacteria, but largely altered the composition of soil fungal communities relative to other treatments (Figure 3). This finding is consistent with previous research showing the responses of soil bacterial and fungal communities to various grassland mowing and management practices (Cui et al, 2020). This effect can be attributed to two factors.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Thus, our experimental findings indicate that deep mowing slightly altered the composition of soil bacteria, but largely altered the composition of soil fungal communities relative to other treatments (Figure 3). This finding is consistent with previous research showing the responses of soil bacterial and fungal communities to various grassland mowing and management practices (Cui et al, 2020). This effect can be attributed to two factors.…”
Section: Discussionsupporting
confidence: 93%
“…As discussed above, our experimental results clearly indicated that deep mowing resulted in a higher redistribution of the soil microbial community among all treatments. Although the stability of microbial communities in grasslands significantly affects soil quality and immunity (McCaig et al, 1999;Bonkowski and Roy, 2005;Otto et al, 2005;Cui et al, 2020), the structure and function of microbial communities in dry grasslands are influenced by numerous physicochemical soil factors (Jangid et al, 2011;Griffiths and Philippot, 2013;Zheng et al, 2019). Microbial communities are, therefore, regarded as a crucial mechanism affecting soil quality, which supports our third hypothesis.…”
Section: Discussionsupporting
confidence: 78%
“…As we expected, N input significantly altered the effects of variation in precipitation patterns on biomass formation and allocation (Figure 1). The primary productivity of the studied grassland was N limited (Yang et al, 2011;Cui et al, 2021); therefore, the N addition significantly enhanced leaf carbon assimilation rate and biomass accumulation (Figures 1A, C). For the aboveground biomass, we detected significant interactions between changes in precipitation amount and N addition, which is in line with the results of a few recently published studies (Li et al, 2019b;Ma et al, 2020).…”
Section: Nitrogen Addition Regulated the Effects Of Changes In Precip...mentioning
confidence: 96%
“…The zonal soil at the study site is classified as Salic Solonetz (World Reference Base for Soil Resources) or an Aqui-Alkalic Halosol (Chinese soil classification) (Ren et al, 2019;Shi et al, 2019). The soil is saline-alkaline with a pH value of 8.0-10.0 (Cui et al, 2021). Table S2 shows the soil's chemical and physical properties at 0-10 cm depth as measured in the control and long-term N addition plots before the precipitation pulse treatments were applied.…”
Section: Site Descriptionmentioning
confidence: 99%